OpenPrescribing: normalised data and software tool to research trends in English NHS primary care prescribing 1998-2016 - Curtis, H; Goldacre, B (BMJ Publishing Group, 2018)
Objectives We aimed to compile and normalise England’s national prescribing data for 1998–2016 to facilitate research on long-term time trends and create an opendata exploration tool for wider use. Design We compiled data from each individual year’s national statistical publications and normalised them by mapping each drug to its current classification within the national formulary where possible. We created a freely accessible, interactive web tool to allow anyone to interact with the processed data. Setting and participants We downloaded all available annual prescription cost analysis datasets, which include cost and quantity for all prescription items dispensed in the community in England. Medical devices and appliances were excluded. Primary and secondary outcome measures We measured the extent of normalisation of data and aimed to produce a functioning accessible analysis tool. Results All data were imported successfully. 87.5% of drugs were matched exactly on name to the current formulary and a further 6.5% to similar drug names. All drugs in core clinical chapters were reconciled to their current location in the data schema, with only 1.26% of drugs not assigned a current chemical code. We created an openly accessible interactive tool to facilitate wider use of these data. Conclusions Publicly available data can be made accessible through interactive online tools to help researchers and policymakers explore time trends in prescribing.